2014
DOI: 10.1186/1475-2859-13-45
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic potential of Escherichia coli BL21 in defined and rich medium

Abstract: BackgroundThe proteome reflects the available cellular machinery to deal with nutrients and environmental challenges. The most common E. coli strain BL21 growing in different, commonly employed media was evaluated using a detailed quantitative proteome analysis.ResultsThe presence of preformed biomass precursor molecules in rich media such as Luria Bertani supported rapid growth concomitant to acetate formation and apparently unbalanced abundances of central metabolic pathway enzymes, e.g. high levels of lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 96 publications
3
88
1
3
Order By: Relevance
“…Gnd, TktA) have previously been found in lower amounts in cells growing under alkaline conditions [27]. We observed down-regulation of both transketolase A and B (TktA, TktB) involved in the nonoxidative branch of the pentose phosphate pathway in contrast to other studies where TktA and TktB have been suggested to be regulated in opposite ways, for instance the TktB gene is induced while TktA is repressed by RpoS [28].…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Gnd, TktA) have previously been found in lower amounts in cells growing under alkaline conditions [27]. We observed down-regulation of both transketolase A and B (TktA, TktB) involved in the nonoxidative branch of the pentose phosphate pathway in contrast to other studies where TktA and TktB have been suggested to be regulated in opposite ways, for instance the TktB gene is induced while TktA is repressed by RpoS [28].…”
Section: Resultscontrasting
confidence: 65%
“…Under alkaline conditions this is executed through active influx of protons and restrained outflux of protons from the cytosol. At aerobic conditions, E. coli produce NADH and FADH 2 through the TCA cycle, these reducing equivalents are oxidized in the respiratory chain, and the electrons generated from the reducing equivalents are subsequently transferred to cytochromes where O 2 is converted to H 2 O [27]. This process is coupled to the formation of a proton motive force (PMF) over the cytoplasmic membrane, which is utilized for ATP generation from ADP and Pi through the ATP synthase complex.…”
Section: Discussionmentioning
confidence: 99%
“…59 alkylAPs may enter cells by diffusion through porins 59 or by active nutrient transporters as in the cases of fosmidomycin, 60 fosfomycin, 61 and D-cycloserine. 62 Nutrient limitation itself may alter expression of transporters that aid cellular uptake for the alkylAP analogs 63 or lacks compounds found in rich medium that may otherwise serve to interfere with transport of the analogs (akin to the inhibited uptake of the antibiotic D-cycloserine by D-alanine through the D-alanine−glycine transport system). 62 Finally, some combination of effects altering cellular metabolism and alkylAP uptake could certainly be at play to cause this striking difference in alkylAP activity accompanying the change in growth environment.…”
Section: Discussionmentioning
confidence: 99%
“…9a), a reduction in AceE levels might be expected, but we observed instead an increase in activity, transcript levels, and transcript half-life. Additionally, transcript levels of aceE have been shown to decrease significantly upon entry into stationary phase (51), and even if this reduction occurs in both the WT and the rnc deletion mutant, the observed increase in the half-life of aceEF-lpd (~5 min compared to ~3 min) could explain the observed increase in PDH activity in early stationary phase in the rnc deletion mutant. The effect of these processing events on transcripts encoding metabolic enzymes is complex because, although RNase III is known to be constitutively expressed (and autoregulates its own mRNA decay [29]), its activity has been shown to be affected by a protein inhibitor as well as by other, unknown factors (5).…”
Section: Discussionmentioning
confidence: 99%